LITERASI INFORMASI PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH KARAWANG MENGENAI MITIGASI BENCANA ABRASI KECAMATAN CIBUAYA - Tsani Abdillah, Zilki; Rizal , Edwin; Yanto, Andri (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2024)
(Objectives) The coastal area of Karawang Regency, in Cibuaya, has been experiencing abrasion since 2017, causing damage to 177 housing units with different levels of damage. To address this issue, the government needs to implement effective mitigation measures, including providing information. This research aims to understand the role of information literacy in reducing disaster risk in the area. This research is how the ability of BPBD Karawang employees to search, evaluate and create information related to abrasion disaster mitigation in Cibuaya kec. To find out the information literacy skills of BPBD Karawang employees in improving employee information literacy in finding relevant information sources according to employee needs, so that BPBD Karawang employees can provide information and knowledge for the community in the Cibuaya area. (Method) This research uses a qualitative method with a case study type. In this context, the data was used to understand and analyze how BPBD Karawang employees use and create information about abrasion disasters, and how they evaluate the information to ensure relevance and accuracy. (Findings) This research shows that BPBD Karawang employees have good information literacy skills in searching, evaluating and creating information related to abrasion disaster mitigation. However, there are still some obstacles in managing disaster data and disseminating information through the website. Therefore, it is necessary to improve access and human resources to manage information on the website and the Prevention and Preparedness field so that the dissemination of disaster information is more effective and comprehensive.